Philoctetes - Sophocles (Greek tragedy in new translations., 2003)
Based on the conviction that only translators who write poetry themselves can properly re-create the celebrated and timeless tragedies of Aeschylus, Sophocles, and Euripides, the Greek Tragedy in New Translations series offers new translations that go beyond the literal meaning of the Greek in order to evoke the poetry of the originals. Under the general editorship of Peter Burian and Alan Shapiro, each volume includes a critical introduction, commentary on the text, full stage directions, and a glossary of the mythical and geographical references in the play. En route to fight the Trojan War.